The ATLAS Experiment at the CERN Large Hadron Collider - Aad, G. (2008)
The ATLAS detector as installed in its experimental cavern at point 1 at CERN is described in this paper. A brief overview of the expected performance of the detector when the Large Hadron Collider begins operation is also presented.